A review of the theory of 3‐D Alfvén (field line) resonances - Elsden, Tom; Wright, Andrew; Degeling, Alex (Frontiers in Astronomy and Space Sciences, 2022)
This review article aims to summarise recent developments in Alfvén resonance theory, with a focus on applications to magnetospheric ultra-low frequency (ULF) waves, though many of the ideas are relevant for applications in other fields as well. The key aspect we treat is how Alfvén resonance manifests in a fully 3-D varying medium. The prerequisite ideas are developed in a reasonably comprehensive introduction, which would be a good starting point for any interested reader looking to gain an understanding of the Alfvén resonance process, as well as where to find associated reading. The main part of the review is split into three sections. We firstly consider results from numerical simulations of relatively simple magnetic field geometries, such as 2-D and 3-D dipoles, to develop the fundamental properties of 3-D Alfvén resonances. Secondly, we review previous simulations in more general magnetic field geometries, reconciling these results with those from the simpler dipole cases. Thirdly, in light of these numerical results, we review theoretical studies using various analytical methods to find approximate solutions to the pertinent magnetohydrodynamic (MHD) equations. The review is concluded with a discussion of these different approaches, as well as linking these ideas to their importance for observations. Finally, we discuss potential future developments in this research area.